الهم والحزن بين القرآن الكريم وعلم النفس : دراسة موضوعية مقارنة - تويجري، هيلة منديل (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2006)
This research aims to study the life and the lifestyle of the well-known preIslamic poet (Hatim al-Ta'i) through his poetry. The poet represents an ideal model of the generosity and the praiseworthy attributes of the Arabs before the Islamic era. Hence, the researcher attempted to extract the moral values from his poetry in order to analyze them objectively. That implies his artistic poetry in terms of forms, rhythm and music, meaning and ideas, emotions and feeling, and, finally, imagination and fictions. The researcher used proper methods in each stage of the research, making use of the poet's collections, previous studies as well as related sources. The research has shown that there is a strong correlation between the poet's poetry and his lifestyle, as demonstrated in his poetic themes that reflect his principles and values, as well as in his smooth and simple styles. This indicates that the poet had advocated the moral objective of poetry as seem in his call for ethics.